2008
DOI: 10.1136/bmj.a2423
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of statins in familial hypercholesterolaemia: a long term cohort study

Abstract: Objective To determine the efficacy of statin treatment on risk of coronary heart disease in patients with familial hypercholesterolaemia.Design Cohort study with a mean follow-up of 8.5 years.Setting 27 outpatient lipid clinics.Subjects 2146 patients with familial hypercholesterolaemia without prevalent coronary heart disease before 1 January 1990.Main outcome measures Risk of coronary heart disease in treated and “untreated” (delay in starting statin treatment) patients compared with a Cox regression model i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
396
1
24

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 652 publications
(427 citation statements)
references
References 16 publications
6
396
1
24
Order By: Relevance
“…Although statin use has proved effective for primary prevention of cardiovascular events,12, 13, 14, 15, 16 the underlying mechanisms are still not well understood because there has been no appropriate analysis. By producing human‐like advanced coronary plaques in our LDLR knockout pigs, we justified, on the basis of histopathologic examination, early statin treatment before the formation of atherosclerotic plaques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although statin use has proved effective for primary prevention of cardiovascular events,12, 13, 14, 15, 16 the underlying mechanisms are still not well understood because there has been no appropriate analysis. By producing human‐like advanced coronary plaques in our LDLR knockout pigs, we justified, on the basis of histopathologic examination, early statin treatment before the formation of atherosclerotic plaques.…”
Section: Discussionmentioning
confidence: 99%
“…Several compelling clinical trials have supported statin treatment as prophylaxis against cardiovascular events 12, 13, 14, 15, 16. With development of our LDLR −/− pigs, we sought to take the next step in the research process to examine the direct effects of statin on the development of plaques, especially advanced plaques.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Therefore, it has been suggested that incidental detection of variants leading to FH should be communicated to the affected individual and the family. 13 In fact, owing to the high frequency of FH, several guidelines recommend programs to systematically unravel variants and to facilitate medical treatment already at young age.…”
Section: Introductionmentioning
confidence: 99%
“…26 However, once a heterozygote form of FH is diagnosed, it can be treated with statins or combined lipidlowering therapies. 27 According to our study findings, patients with a family history of FH were less likely to make progress in overall lipid parameter variations. Further detailed evaluation may be required among these patients due to inadequate improvement of variance, and more aggressive types of treatment could be applied.…”
Section: Discussionmentioning
confidence: 56%